2003
DOI: 10.1097/01.brs.0000058946.64222.92
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Sox9 Gene Therapy for Intervertebral Degenerative Disc Disease

Abstract: Study Design-A new recombinant adenoviral vector expressing Sox9, a chondrocyte-specific transcription factor, was tested in a chondroblastic cell line and primary human intervertebral disc cells in vitro. Direct infection of intervertebral disc cells then was assessed in a rabbit model.Objectives-To deliver a potentially therapeutic viral vector expressing Sox9 to degenerative human and rabbit intervertebral discs cells, and to assess the effect of Sox9 expression on Type 2 collagen production.Summary of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(100 citation statements)
references
References 44 publications
2
94
0
4
Order By: Relevance
“…Although different markers have been suggested for NP cells in the last few years, no ideal single marker has been identified so far, thus leading to the conclusion that the expression of a set of genes needs to be analyzed, such as HIF-1 (hypoxia induced factor) (Rajpurohit et al, 2002), GLUT-1 (glucose transporter) (Rajpurohit et al, 2002), MMP2 (matrix metalloproteinase 2) (Rajpurohit et al, 2002), CD24 (glycosylphosphat-idylinositol-anchored cell surface protein) (Fujita et al, 2005) and Sox9 (Paul et al, 2003). Both HIF-1 and GLUT-1 are related to the NP metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although different markers have been suggested for NP cells in the last few years, no ideal single marker has been identified so far, thus leading to the conclusion that the expression of a set of genes needs to be analyzed, such as HIF-1 (hypoxia induced factor) (Rajpurohit et al, 2002), GLUT-1 (glucose transporter) (Rajpurohit et al, 2002), MMP2 (matrix metalloproteinase 2) (Rajpurohit et al, 2002), CD24 (glycosylphosphat-idylinositol-anchored cell surface protein) (Fujita et al, 2005) and Sox9 (Paul et al, 2003). Both HIF-1 and GLUT-1 are related to the NP metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Even more interesting is the expression of Sox9 in 3D cultures. Paul et al (2003) studied the potential use of a recombinant adenoviral vector expressing Sox9 in human disc cells among others. It was shown that the expression of the chondrocyte-specific transcription factor clearly stimulated collagen type II synthesis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…A chondrogenic transcription factor Sox9 plays a major role in an increased level of chondrogenesis in the mouse (Akiyama 2011;Tew and Clegg 2011) in particular by activating co-expression with collagen type II (Ng et al 1997;Marshall and Harley 2000;Davies et al 2007). Various gene therapy approaches using viral methods to over-express Sox9 resulted in significant improvements in the production of cartilaginous matrix by articular chondrocytes, bone marrow-derived stem cells and nucleus pulposus cells (Paul et al 2003;Tsuchiya et al 2003;Tew et al 2005). Evidence indicated Quantification of DNA content, GAG production, and collagen content of cells: (A) The DNA content of chondrocytes cultured in vitro with 15 µg/ml, 30 µg/ml or 60 µg/ml taurine for 2, 4 or 6 days; (B) GAG (mg) normalized to DNA (mg); (C) The total collagen content (µg).…”
mentioning
confidence: 99%
“…Adenovirus vector was used to transfer the LMP-1 gene in anulous fibrosus cells and chondrocytes, where it similarly increased proteoglycan and collagen production (43). Transfection of degenerated human intervertebral disc cells with an adenovirus vector expressing SOX9 resulted in increased synthesis of collagen type II (44), restored the height of the degenerative rabbit intervertebral disc and promoted the expression of proteoglycan and collagen type II when administered with OP-1 as a dual gene therapy (45).…”
Section: Factors Enhancing Matrix Synthesismentioning
confidence: 99%